Welfare Classification of Muslim Majority Communities using Decision Tree Algorithm - Naufal Berlian; Andi Malia Fadilah Bahari; Jidan Ramdani; Rico Candra; Intan Permata Sari; Maulana Aditya (Khazanah Journal of Religion and Technology, 2023)
Community welfare is a benchmark of various conditions that can represent a quality community life. It is undeniable that welfare in a comprehensive sense can be realized if certain economic conditions can be achieved, one of which is prosperity. Economic freedom is a framework in which principles compatible with the ideals of prosperity are implemented in economic institutions and processes. Important components in economic freedom such as size of government, legal system and property rights, sound money, freedom to trade internationally, and regulation have a significant influence on the welfare of the people of a country. This study aims to examine the effect of economic freedom on the welfare of the people in several countries with the Muslim majority population. By using unsupervised learning methods and decision tree algorithms in the classification, the experiment result found that 35% of countries with a majority Muslim population in the world were classified as Moderately Free.